GAMBARAN TINGKAT ANSIETAS ANAK USIA SEKOLAH SAAT MENGALAMI MENARCHE - Livana PH; Novi Indrayati; Eka Yuliyanti (Jurnal Kesehatan, 2019)
Menarche is menstruation which occurs first as a sign of maturity of a woman's reproductive organs. Menarche events that tend to be earlier, when children have not reached a maturity of mind coupled with a factor of lack of knowledge raise a variety of psychological responses to girls, namely anxiety. The purpose of this study was to describe the anxiety level of school-age children in the village when experiencing menarche. The design of this study used a cross-sectional approach, with a sample of 30 female students who had experienced menarche. The sampling technique uses total sampling. Data analysis using descriptive analysis. The results of the study showed that the majority of school-age children in the village experienced moderate anxiety. Based on the results of the study it is suggested that nurses need to carry out their role as educators zx and counselors by providing health education to school-age children, especially providing information regarding menarche, so that children are better prepared to face menarche, so as not to cause anxiety.ABSTRAKMenarche yaitu menstruasi yang terjadi pertama kali sebagai tanda kematangan alat reproduksi wanita. Kejadian menarche yang cenderung lebih awal, ketika anak belum mencapai kedewasaan pikiran ditambah dengan faktor kurangnya pengetahuan memunculkan bermacam respon psikologis pada anak perempuan yaitu ansietas. Penelitian ini untuk mengetahui gambaran tingkat ansietas anak usia sekolah di desasaat mengalami menarche. Jenis penelitian kuantitatif dengan metode deskriptif, dengan jumlah sampel 30 siswi yang sudah mengalami menarche. Teknik pengambilan sampel menggunakan total sampling. Analisis data menggunakan analisis deskriptif. Hasil penelitian diperoleh bahwa mayoritas anak usia sekolah di desa menalami ansietas sedang (56,7%). Berdasarkan hasil penelitian disarankan bahwa perawat perlu untuk melakukan perannya sebagai edukator dan konselor dengan memberikan pendidikan kesehatan pada anak usia sekolah terutama memberikan informasi terkait menarche, agar anak lebih siap dalam menghadapi menarche, sehingga tidak menimbulkan kecemasan.